2012
DOI: 10.1021/jf300827q
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three DNA Extraction Methods for Feed Products and Four Amplification Methods for the 5′-Junction Fragment of Roundup Ready Soybean

Abstract: Three methods of DNA extraction from feed products and four detection methods for the 5'-junction fragment of genetically modified (GM) Roundup Ready soybean (RRS) were compared and evaluated. The DNA extraction methods, including cetyltrimethylammonium bromide (CTAB), sodium dodecyl sulfate (SDS), and guanidine hydrochloride (Kit), were assessed for their yields and purity of DNA, extraction time, and reagent cost. The DNA yields of CTAB, SDS, and Kit were 52-694, 164-1750 and 23-105 ng/mg sample, and their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Similarly, the results of Herzallah (2012) showed that in Jordan, 5.4 % of the total food and feed tested samples were GM positive. The prevalence of GM materials in food and feed industries is the subject of ongoing studies in many countries (Tung-Nguyen et al 2009;Wang et al 2012;Herzallah 2012;Fernandes et al 2014). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the results of Herzallah (2012) showed that in Jordan, 5.4 % of the total food and feed tested samples were GM positive. The prevalence of GM materials in food and feed industries is the subject of ongoing studies in many countries (Tung-Nguyen et al 2009;Wang et al 2012;Herzallah 2012;Fernandes et al 2014). …”
Section: Resultsmentioning
confidence: 99%
“…DNA extraction methods The DNA extraction methods were chosen from those previously reported to be successful for food and feed products (Mafra et al 2008;Peano et al 2004;Smith et al 2007;Jasper et al 2009;Wang et al 2012). Total DNA was isolated with four commercial kits: Foodproof GMO Sample Preparation (Biotecon Diagnostics GmbH, Potsdam, Germany), DNeasy Plant Mini (Qiagen, Valencia, CA), Wizard (Promega, Madison, WI), and Genespin (GeneScan, Freiburg, Germany) as described by the manufacturers' instructions, and by the CTAB (Cetyltrimethylammonium bromide) method with some modifications, specifically adding RNase A (10 mg/mL) in the DNA precipitation step (Mafra et al 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genomic DNA of NL‐11 was extracted by using the CTAB method (Wang et al , ), and the 16S rDNA coding region was amplified through PCR. The forward PCR primer was 27F (5′‐AGAGTTTGATCC/ATGGCTCAG‐3′), and the reverse PCR primer was 1492R (5′‐TACGGTTACCTTGTTACGACTT‐3′).…”
Section: Methodsmentioning
confidence: 99%
“…Lines 1-9: 100 pb DNA pattern, negative control, conventional maize sample, 0.1%, 0.5%, 1.0%, 5.0% and 10.0% contamination with TC1507 transgenic maize and TC1507 sample. when compared to those of conventional PCR (WANG et al, 2012). For tests that require more precision, real time PCR is recommended over conventional PCR.…”
Section: Pcr Multiplexmentioning
confidence: 99%